2011
DOI: 10.1590/s0100-40422011000300026
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e validação de método analítico para determinação do teor de sinvastatina em cápsulas magistrais

Abstract: Recebido em 23/4/10; aceito em 9/9/10; publicado na web em 8/12/10 DEVELOPMENT AND VALIDATION OF ANALYTICAL METHOD FOR DETERMINATION OF SIMVASTATIN IN CAPSULES.Simvastatin is an oral anti-hyperlipidemic that has been widely used to reduce the cardiovascular disease risk. There isn't any pharmacopoeic method to assay this drug in capsules. It was proposed and validated a method for determining the content of simvastatin in capsules by UV/visible spectrophotometry (λ = 237 nm), a more affordable method for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
0
5
0
10
Order By: Relevance
“…9,10 In this context, many studies and information are reported about compounding, such as the assessment of the final product quality, comparison with industrial formulations and evaluation of manipulation process. [11][12][13][14] It is noteworthy that compounding pharmacies can produce their based pharmaceutical formulations recommended in standard reference sources or provided by manufacturers of pharmaceutical raw materials. However, non-official formulations may exhibit variations in their compositions when manipulated in different pharmacies, leading to varied products.…”
Section: Implementation Of a Spectrofluorimetric Methods To The Determmentioning
confidence: 99%
“…9,10 In this context, many studies and information are reported about compounding, such as the assessment of the final product quality, comparison with industrial formulations and evaluation of manipulation process. [11][12][13][14] It is noteworthy that compounding pharmacies can produce their based pharmaceutical formulations recommended in standard reference sources or provided by manufacturers of pharmaceutical raw materials. However, non-official formulations may exhibit variations in their compositions when manipulated in different pharmacies, leading to varied products.…”
Section: Implementation Of a Spectrofluorimetric Methods To The Determmentioning
confidence: 99%
“…É importante que esses métodos analíticos sejam de baixo custo, rápidos e precisos. 9,12 Neste trabalho, o objetivo está focado em validar dois métodos analíticos, rápidos, seguros e de baixo custo, que podem ser aplicados tanto em estabelecimentos como farmácias magistrais, como também em indústrias farmacêuticas. …”
Section: Figura 1 Estrutura Química Da Sulfassalazinaunclassified
“…A análise da variância (ANOVA) nos permite avaliar a linearidade do método e a validade da regressão. 12 Através do teste F é possível confirmar o modelo linear da curva, considerando a hipótese de que o coeficiente angular da curva seja diferente de zero, o valor de F calculado deve ser maior que o F crítico ou de significação, nesse caso, o valor encontrado para F calculado foi de 5597,4 e o F de significação ou crítico igual a 1,61 x 10 -18 , confirmando, assim, a regressão nas três curvas de calibração. Neste caso, pode confirmar, com 95% de confiância, que o modelo é linear e que a inclinação da reta não é nula.…”
Section: Método Espectrofotométricounclassified
“…Desta forma, é essencial o controle de qualidade do produto acabado nas farmácias de manipulação, pois um dos parâmetros que mais comumente apresentam desvios da qualidade é a quantidade de fármaco determinada no doseamento. 6,7 Além disso, a partir do estabelecimento da Resolução da Diretoria Colegiada (RDC) nº 33, em 2001, as Farmácias que manipulam formas farmacêuticas passaram a realizar ou terceirizar os ensaios de controle de qualidade dos insumos e dos produtos acabados e, em 2007, com a publicação da RDC nº 67, a prioridade para a realização destes ensaios se concentrou em fármacos cuja dosagem é igual ou inferior a 5 mg; desta forma, é essencial o desenvolvimento e o domínio de uma técnica analítica para determinação destes fármacos, entre eles a tibolona, em formulações obtidas em farmácias de manipulação. 8,9 Na literatura foram encontrados estudos que empregam métodos para o doseamento de tibolona e metabólitos em fluidos biológicos e ensaios de dissolução.…”
Section: Introductionunclassified